Innovation in The Use of Organic Waste for Biobattery and Biogas Production at TPS3R Lamongan - Fadli, Ulfa Mahfudli; Ula, Rahmah Arfiah; Fatayah; Samsiyah, Achsani Ira; Efendi, Aprielia Inzal Fillah Addurrotul (TAAWUN, 2025)
Organic waste that accumulates in the 3R Waste Processing Site (TPS3R) environment needs to be utilized as well as possible. The purpose of this community service activity is to utilize energy from organic waste as the main raw material for making biobattery and biogas. The final result of this community service is a tool that can convert energy from organic waste to electricity (biobattery) and produce gas (biogas). The community service method uses socialization and technology application workshops by assembling tools and materials. Biobattery and biogas equipment, if operated every day, can increase the utilization of organic waste by 17 kg, with 5 kg for biobattery and 12 kg for biogas. Biobattery cells containing around 100 mL of organic waste can produce a maximum voltage of 0.9 Volts and a maximum electric current of 6 mA. Biogas itself requires a sorting process and a fermentation process whose time is adjusted to the presence or absence of organic waste stock at TPS3R. The initial Biogas Place (Digester) requires 600 kg of organic waste. This community service work is expected to inspire the community, especially the Sekar Manfaat Sekaran Lamongan TPS3R Team, to better manage the waste in their surroundings.